Imagining Iraq Literature in English and the Iraq Invasion - Gupta, Suman. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
In the run-up to, during and after the invasion of Iraq a large number of literary texts addressing that context were produced, circulated and viewed as taking a position for or against the invasion, or contributing political insights. This book provides an in-depth survey of such texts to examine what they reveal about the condition of literature.